2005
DOI: 10.1118/1.1954908
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of x‐ray scatter properties in a dedicated cone‐beam breast CT scanner

Abstract: The magnitude of scatter contamination on a first-generation prototype breast computed tomography (CT) scanner was evaluated using the scatter-to-primary ratio (SPR) metric. The SPR was measured and characterized over a wide range of parameters relevant to breast CT imaging, including x-ray beam energy, breast diameter, breast composition, isocenter-to-detector distance, collimated slot thickness, and grid ratio. The results demonstrated that in the absence of scatter reduction techniques, the SPR levels for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
141
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(154 citation statements)
references
References 58 publications
13
141
0
Order By: Relevance
“…Other authors have shown that for some configurations, bowties are beneficial in terms of SPR reduction and image uniformity. 43,47,54,60 Bowties were omitted from the current study because they are not commonly used in all configurations studied here, to avoid further increasing the already large parameter space, and to maintain the focus of the current work on effects of system geometry in and of itself. Similarly, the simulations did not account for the effects of finite focal spot size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have shown that for some configurations, bowties are beneficial in terms of SPR reduction and image uniformity. 43,47,54,60 Bowties were omitted from the current study because they are not commonly used in all configurations studied here, to avoid further increasing the already large parameter space, and to maintain the focus of the current work on effects of system geometry in and of itself. Similarly, the simulations did not account for the effects of finite focal spot size.…”
Section: Discussionmentioning
confidence: 99%
“…There is therefore no simple, nominal choice of filter for each configuration that would permit a fair comparison across this range of geometry, object size, and kVp. Rather, the design of bowtie filters optimal to a particular configuration is a continuing area of work, with results indicating potential advantages in x-ray scatter for some configurations (e.g., breast CT 43 and Linac CBCT 47,60 ). For simplicity in an already broad space of parameters considered below, the simulations considered scenarios without a bowtie.…”
Section: Iib Cbct System and Object Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gantry rotates over 360°in the horizontal plane around the breast and acquires 500 conebeam projection images in 16.6 s. Each breast is scanned separately and the mean fibroglandular radiation dose delivered to the breast was constrained to be the same as twoview mammography. [16][17][18][19][20][21][22] The low-dose acquisition of the breast data as well as the cone-beam geometry of the CT system results in image degradation due to scatter radiation and considerable quantum noise. Therefore correction of scatter and noise is a necessary part of this project because the nonuniformity of the background may cause the denser tissue ͑fibroglandular tissue͒ values to be lower than the less-dense ͑adipose tissue͒ values and vice versa.…”
Section: Iib Breast Ct Data Acquisition and Image Processingmentioning
confidence: 99%
“…There are several groups currently researching dedicated breast CT at the University of California at Davis, [16][17][18][19][20][21][22] Duke University, [23][24][25][26][27][28][29][30][31] University of Rochester, [32][33][34][35][36] University of Massachusetts Medical School, [37][38][39] and University of Texas M.D. Anderson Cancer Center.…”
Section: Iib Breast Ct Data Acquisition and Image Processingmentioning
confidence: 99%